The political theology of Schelling - Das, Saitya Brata (New perspectives in ontology., 2016)
Saitya Brata Das rigorously examines Schelling's theologico-political works and sets his thought against his more dominant contemporary, Hegel. Das argues that Schelling inaugurates a new thinking outside of Occidental metaphysics, by a paradoxical manner of exit, which prepares for the post-metaphysical philosophy of Martin Heidegger, Franz Rosenzweig and Jacques Derrida. This new reflection, outside of the Universal world-historical politics of modernity, is achieved by re-thinking religion as eschatology. Intervening in contemporary debates on post-secularism and the return to religion, Das shows that religion, in an essential sense, always opens up infinitude from the heart of finitude, to an irreducible outside of the profane order of worldly hegemonies. Religion here assumes a negative political theology of exception without sovereign power.